From collapse to consolidation: salvage of lateral plate failure in a medial-deficient distal femur fracture - Wagh, Suyog; Michael, Aibin B.; Ramteke, Tushar; Nair, Pradeep; Goregaonkar , Arvind (International Journal of Research in Orthopaedics, 2025)
Distal femur fractures with medial metaphyseal deficiency pose significant biomechanical challenges, and lateral plating alone may be insufficient to resist varus forces. We reported the case of a 40-year-old male who sustained a distal femur extra-articular fracture with substantial medial cortical bone loss. Initial fixation with a lateral locking plate and cancellous graft failed due to early, unadvised weight bearing, resulting in varus collapse and plate deformation within one week. Revision surgery included removal of failed implants, debridement, and application of a longer lateral locking plate, combined with reconstruction of the medial column using an autologous fibular strut graft inserted intramedullary. A contoured medial plate was added to create a dual-plating construct. Postoperative rehabilitation followed a protected, staged weight-bearing protocol. Radiographs at 3 months demonstrated bridging callus, and by one year the patient achieved painless independent ambulation with maintained alignment and no implant-related complications. This case illustrates the mechanical vulnerability of lateral-only constructs in medial-deficient distal femur fractures and highlights the benefits of dual plating with structural grafting in both primary and salvage settings. Augmenting the medial column improves load sharing, reduces varus stress on the lateral plate, and enhances construct stability. Early recognition of at-risk patterns, appropriate implant selection, and cautious rehabilitation are critical to preventing fixation failure. Timely revision using dual plating and graft support can successfully salvage early collapse and restore function.